Neo-clerodane diterpenoid, a new metalloprotease snake venom inhibitor from Baccharis trimera (Asteraceae): anti-proteolytic and anti-hemorrhagic properties - Januario, A. H.; Santos, S. L.; Marcussi, S.; Mazzi, IV; Pietro, RCLR; Sato, D. N.; Ellena, J.; Sampaio, S. V.; Franca, S. C.; Soares, A. N. (Elsevier B.V., 2004)
Many plants are used in traditional medicine as active agents against various effects induced by snakebite. Few attempts have been made however to identify the nature of plain natural products with anti-ophidian properties. Baccharis trimera (Less) DC (Asteraceae), known in Brazil as carqueja. has been popularly used to treat liver diseases. rheumatism. diabetes, as well as digestive, hepatic and renal disorders. The active component was identified as 7alpha-hydroxy-3,13-clerodadiene-16,15:18,19-diolide, C20H28O5, (clerodane diterpenoid, Bt-CD). We report now the anti-proteolytic and anti-hemorrhagic propenies against snake venoms of a Bt-CD inhibitor from B. trimera. Bt-CD exhibited full inhibition of hemorrhage and proteolytic activity caused by Bothrops snake venoms. The inhibitor was able to neutralize the hemorrhagic, fibrinogenolytic and caseinolytic activities of class P-I and III metalloproteases isolated from B. neuwiedi and B. jararacussu venoms. No inhibition of the coagulant activity was observed. Bt-CD also partially inhibited the edema induced by other crude venoms, metallopronteases, basic and acidic phospholipases A(2). To further elucidate the inhibitory specificity of Bt-CD against metalloproteases isolated from snake venoms, a deeper understanding of its Structure and function is necessary. Furthermore, the potential use of these inhibitors to complement anti-venom as an alternative treatment of snakebite envenomations needs to be evaluated in future Studies. (C) 2004 Elsevier B.V.. All rights reserved.
Keywords: Baccharis trimera; clerodane diterpenoid; snake venoms; anti-metalloproteases; anti-hemorrhagic activity; anti-proteolytic activity; anti-ophidian activity